(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the great experiences of the legal documents by civil protection in the economy of the Russian Federation. To protect responsible persons, population and territories from emergency situations in the economic buildings, to make preparation to create the legal documents, to prevent and eliminate of emergency situations, to create the normative-legal documents some suggestions are given by civil protection in economic buildings.